Fd1 = {AB --> C, D --> E, E --> C}
Fd2 = { AB --> C, D --> E, AB --> E, E --> C}
are these two FD's are equivalent or not, i think they are. But in the answer it's shown as not equivalent.
You cannot produce AB → E from dependencies in the first set.
To mathematically prove their (in)equivalence, you should build closures for both sets and compare the closures.
There are a few simple induction rules to build the a closure. Quoting Wikipedia on Functional Dependency, the axioms are:
with by a few rules that follow from them:
Using these rules and axioms, one can build a closure for a FDS.
Omitting trivial dependencies (the ones where right side is included into left side), first set { AB → C (1), D → E (2), E → C (3) } gives:
AB → C (1)
ABD → CE, ABD → C, ABD → E (composition 1+2, decomposition)
ABDE → CE, ABDE → C (composition 1+2+3, decomposition)
ABE → C (composition 1+3)
D → E, D → C, D → CE (2, transitivity 2+3, union)
DE → CE, DE → C (composition 2+3, decomposition)
E → C (3)
And the second set { AB → C (1), D → E (2), E → C (3), AB → E (4) } gives:
AB → C, AB → E, AB → CE (1, 4, union 1+4)
ABD → CE, ABD → C, ABD → E (composition 1+2, decomposition)
ABDE → CE, ABDE → C (composition 1+2+3, decomposition)
ABE → C (composition 1+3)
D → E, D → C, D → CE (2, transitivity 2+3, union)
DE → CE, DE → C (composition 2+3, decomposition)
E → C (3)
The second closure has AB → E, AB → CE
, which is not present in the first closure, therefore original sets are different.